2005
DOI: 10.1128/aac.49.4.1542-1552.2005
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Effects of Novel XF Porphyrin Derivatives on Prokaryotic and Eukaryotic Cells

Abstract: The worldwide rise in the rates of antibiotic resistance of bacteria underlines the need for alternative antibacterial agents. A promising approach to the killing of gram-positive antibiotic-resistant bacteria of the skin uses light in combination with a photosensitizer to induce a phototoxic reaction. Different concentrations (0 to 100 M) of porphyrin-based photosensitizers (CTP1, XF70, and XF73) and different incubation times (5 min, 1 h, and 4 h) were used to determine phototoxicity against two methicillin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
139
1
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(151 citation statements)
references
References 66 publications
7
139
1
4
Order By: Relevance
“…There have been several previous literature reports comparing the PDI of MRSA with that of S. aureus. Maisch et al 15 used XF porphyrins as antimicrobial PSs and found identical killing of MRSA (and methicillin-resistant S. epidermidis to that found with the wild-type strains). Wainwright et al 16 found that PDI with phenothiazinium dyes killed MRSA somewhat less efficiently than wild-type S. aureus strains.…”
Section: Discussionmentioning
confidence: 87%
“…There have been several previous literature reports comparing the PDI of MRSA with that of S. aureus. Maisch et al 15 used XF porphyrins as antimicrobial PSs and found identical killing of MRSA (and methicillin-resistant S. epidermidis to that found with the wild-type strains). Wainwright et al 16 found that PDI with phenothiazinium dyes killed MRSA somewhat less efficiently than wild-type S. aureus strains.…”
Section: Discussionmentioning
confidence: 87%
“…One promising technique is the photodynamic inactivation of bacteria, in which the generation of singlet oxygen plays a major role (28,29). To enhance this approach, we investigated the generation and decay of singlet oxygen in bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Apesar do considerável progresso que tem sido obtido nos tratamentos de infecções, é preocupante o crescente número de bactérias patogênicas resistentes a antibióticos no mundo todo 16 , o que, segundo Hamblin e Hasan 7 , pode levar ao fim de um extenso período que inclui os últimos 50 anos, chamado de "era do antibiótico". As bactérias multiplicam-se muito rapidamente e uma mutação que ajude um único micróbio a sobreviver na presença de um antibiótico rapidamente se tornará predominante na população microbiana.…”
Section: Bactériasunclassified
“…Com relação à eficiência da inativação bacteriana, é conhecido que bactérias Gram-positivas (+) são geralmente mais susceptíveis à PDI e as espécies Gram-negativas (-) são significantemente resistentes a muitos fotossensibilizadores comumente usados em TFD de tumores 16 .…”
Section: Figura 4 Estrutura Química Da Rosa De Bengala (A) Azul De unclassified